A metabolomics approach to profiling the cardioprotective effect of LCZ696, an angiotensin receptor-neprilysin inhibitor, on ischemia induced heart failure. Issue 46 (5th June 2017) - Xia, Yan; Chen, Zhangwei; Chen, Ao; Lu, Danbo; Jia, Jianguo; Zou, Yunzeng; Qian, Juying; Ge, Junbo
Abstract : Heart failure is a chronic disease, but no clinically approved metabolite biomarkers have been identified. We conducted a metabolomics study to investigate the disease and the efficacies of LCZ696. Abstract : Heart failure is one of the most common chronic diseases in the world, particularly among the elderly, yet, no clinically approved metabolite biomarkers have been identified so far. To address this issue, we conducted a liquid-chromatography study with time-of-flight mass spectrometer (LC/Q-TOF-MS)-based metabolomics to investigate heart failure and to assess the efficacies and mechanisms of LCZ696, which is a novel angiotensin receptor neprilysin inhibitor in treating heart failure in mice induced by coronary artery ligation. Based on unsupervised principal component analysis, a clear separation was observed between the heart failure and sham-operated group, which revealed that heart failure disturbed the metabolism of endogenous substances and significantly altered the heart metabolite fingerprints. After LCZ696 treatment, the metabolomics profile found in heart failure was significantly reversed, shifting much closer to sham controls, confirming that LCZ696 had therapeutic effects in heart failure. Metabolomic pathway analysis revealed that several pathways including fatty acid metabolism, lipid metabolism, glucose metabolism, and amino acid metabolism were significantly altered in heart failure mice. Consequently, it was inferred that LCZ696 shows therapeutic efficacy in heart failure by restoring these disturbed metabolic pathways, especially the ones related to energy metabolism. To conclude, the present study provides a new methodological approach for understanding heart failure and LCZ696 mechanisms relevant for heart failure treatment.